Determinant Factors of Safety and Health Behavior in Students: A Systematic Review - Eka Rosanti; Wiwik Eko Pertiwi; Sri Achadi Nugraheni (UPT Publikasi Ilmiah Universitas Islam Bandung, 2025)
Schools as educational institutions need to create safe and healthy learning spaces for teachers and students. Currently, many articles discuss student safety and healthy behavior, recognizing that schools are vulnerable to risk factors, hazards, and disasters. This study aims to identify and analyze the determinants of students' safety and health behavior from 2020 to 2024. The systematic literature review method was used to identify articles with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) approach to obtain 23 articles from 4 databases, that are Scopus, Science Direct, Proquest, and PubMed with inclusion criteria are journals published in January 2020–October 2024, in English, open access, and focused on occupational health and safety behavioral factors in students. Four themes, each comprising 14 indicators, were identified as determinants of students' safety and health behavior. The discussion fluctuates each year, involving most countries, and the majority discuss university education. The highest indicator is training (T) with eight articles, followed by technology (Te) with seven articles. This study found that the safety and healthy behavior of students when viewed from the socio-ecological model is grouped into individual (5), interpersonal (1), institutional (4), community (2), and policies macro environment (2). According to Lawrence W. Green's behavioral theory, predisposing factors accounted for 36% (5), supporting factors for 57% (8), and reinforcing factors for 7% (1). Student safety and health behavior are influenced by training, psychological models, and school community support. These findings highlight the need for continuous training and a strong safety culture as the basis for evidence-based educational policies. The conclusion of this systematic literature review is expected to serve as input for policymakers in developing strategic and practical guidelines for safety and health programs in educational units.